ANDROGENETIC ALOPECIA: A REVIEW OF CURRENT THERAPEUTIC OPTIONS - Wiktoria Auguścik,; Katarzyna Bielawska,; Aleksandra Tlak, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Androgenetic alopecia (AGA) is the most common form of hair loss, caused by a genetically determined hypersensitivity of hair follicles to dihydrotestosterone (DHT). This condition affects both sexes and significantly impacts quality of life.Aim: The aim of this review is to present current and new therapeutic options for the treatment of androgenetic alopecia.Methods: A literature review was conducted in PubMed, Scopus and Google Scholar databases from 2015 to 2025, covering 19 publications on pharmacotherapy, supportive and surgical methods.Results: Minoxidil (topical and oral) and 5α-reductase inhibitors are the most effective methods. Adjunctive therapies such as platelet-rich plasma, microneedling, LLLT, and spironolactone enhance treatment efficacy. In advanced cases, hair transplantation techniques are the solution.Conclusions: The treatment of AGA requires individualisation, combination therapy and long-term monitoring. The development of regenerative methods creates new therapeutic perspectives.